(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
Today, sustainable development has become a key item on the global agenda. In this development process, the financial system plays an essential role, as the effective allocation of economic resources is crucial for achieving sustainability goals. In achieving sustainable progress, Environmental, Social, and Governance (ESG) principles are of significant importance in managing financial resources. For this system to function effectively, a certain legal and regulatory framework is necessary. According to research conducted in the field of project financing, in countries where such systems have been implemented, it has been proven that inadequate legal and regulatory frameworks and the limited protection of creditors’ rights reduce efficiency.